Efficacy and safety of auricular point acupressure treatment for gastrointestinal dysfunction after laparoscopic cholecystectomy: study protocol for a randomized controlled trial. Issue 1 (December 2016) - Tan, Yuhua; Zhao, Ye; He, Tian; Ma, Yueshen; Cai, Wang; Wang, Yandong
Abstract Background Practitioners of traditional Chinese medicine know that auricular point acupressure (APP) using vaccaria seeds on the large intestine point (CO7) has a significant effect on postoperative gastrointestinal dysfunction. A standardized, clinical, research design will transform this clinical experience into scientific evidence, thus providing a basis to promote the wider use of this therapy. We aim to carry out a double-blind, randomized, controlled trial (RCT) to evaluate the efficacy and safety of APP treatment for gastrointestinal dysfunction after laparoscopic cholecystectomy. Methods/design This study is a randomized, double-blind, controlled, single-center, clinical, pilot trial. It has been designed according to the Consolidated Standards of Reporting Trials (CONSORT 2010) guidelines as well as the Standards for Reporting Interventions in Controlled Trials of Acupuncture (STRICTA). Study subjects are being selected from among hospitalized patients who have undergone laparoscopic cholecystectomy at the Department of Minimally Invasive Surgery of Tianjin Nankai Hospital. Qualified subjects will be assigned randomly either to the APP group or to the APP sham stimulation group on the basis of random numbers generated using SPSS 19.0. A specifically appointed investigator will be responsible for the randomization. The APP therapy (or sham stimulation) will be performed 6 h after surgery and every 12 h subsequently; six sessions will be conducted, each lasting 3 min. The first evaluation will be performed immediately before the first treatment (6 h after surgery) and, then, every 12 h for seven evaluations. The primary outcome is the time to first passage of flatus after surgery; the secondary outcome measures are abdominal distension, nausea, vomiting, time to first defecation, psychological status, and quality of life. Discussion This pilot trial is a standardized, scientific, clinical trial designed to evaluate the efficacy and safety of APP treatment—using vaccaria seeds on CO7—for gastrointestinal dysfunction after laparoscopic cholecystectomy. We aim to provide objective evidence to promote this therapy in clinical practice. Trial registration Chinese Clinical Trial Registry, ChiCTR-IPR-15007643 . Registered on 14 December 2015.